International Capital Markets, Oil Producers and the Green Paradox - Gerard C. van der Meijden; Rick Van der Ploeg; Cees A. Withagen (Center for Economic Studies and ifo Institute (CESifo), 2014)
A rapidly rising carbon tax leads to faster extraction of fossil fuels and accelerates global warming. We analyze how general equilibrium effects operating through the international capital market affect this Green Paradox. In a two-region, two-period world with identical homothetic preferences and without investment, the global interest rate falls and the Green Paradox weakens. With investment or a relatively more impatient oil-importing region, the Green Paradox may be strengthened because the future oil demand function shifts downward or because the interest rate rises. If the oil-importing region is very much more patient than the oil-exporting region, the Green Paradox may be reversed but in our calibrated model the effects are tiny. With exploration and endogenous initial oil reserves, a future carbon tax lowers cumulative oil extraction in partial equilibrium. If the boost to current oil extraction is weakened, strengthened or reversed in general equilibrium, so is the fall in cumulative extraction. A partial and general equilibrium welfare analysis of a future carbon tax, both for full and partial exhaustion, is given.
Keywords: D90; H20; Q31; Q38; 330; global warming; Green Paradox; Hotelling rule; oil importers; oil producers; investment; capital markets; carbon tax; exploration investment; general equilibrium